Qualitative and quantitative transformations of physical-chemical parameters in aged cachaças (Research, Society and Development, 2024)
The cachaça has been aged in barrels made from different types of wood in order to provide not only added value to the product but also unique organoleptic experiences for its consumers. This aging process has several singular nuances that make each product unique, which can be related to the species of wood, the cut used in making the barrels, the temperature and humidity of the aging location, the aging time, among other factors. Despite the many variables in the process, it is possible to determine the main transformation reactions that occur during this stage of production. The objective of this work was to perform a qualitative and quantitative evaluation of the compounds present in different samples of aged cachaças to better understand the transformations that occur during the aging period. The cachaças under study showed differences in chemical composition, a fact that was expected since the aging process tends to add compounds that modify the organoleptic characteristics of the beverages. It is worth noting that all samples comply with current legislation regarding the parameters analyzed. The beverages showed distinct values in the phenolic compounds analyzed, both in terms of concentration and identification. The cachaça aged in oak presented syringaldehyde (1.66 mg L-1) as the major compound, amburana showed coumarin (4.52 mg L-1), jequitibá exhibited vanillin (0.12 mg L-1), and the oak/chestnut blend had gallic acid (1.24 mg L-1) and syringaldehyde (2.08 mg L-1). Thus, it can be inferred that these major compounds found are potential chemical markers for the woods studied.